Bioethanol Production from Organic Wastes by Using the Newly Isolated Bacteria Klebsiella oxytoca (SAR) - Mustafa, Sama A.; Al-Azawi, ahmed (Iraqi Journal of Science, 2025)
This study was carried out to study the ability of producing bioethanol from latus leaves as an organic waste rich with cellulose. The study results show that the pre-treatments (alkali and acidic pre-treatments) increase the amount of the sugar released in the media that is accessible for the bacteria to use in the fermentation. The newly recorded bacteria Klebsiella oxytoca (SAR) was able to ferment the latus leaves and produce bioethanol. The amount of ethanol produced by the bacteria was increased as the experiment period increased, until the seventh day when it began to decrease. In order to increase the purity of the acquired bioethanol, the resulted ethanol was distilled to reduce the water content in the solution, while the dehydration process did not have any effect on bioethanol purity.